Customer Satisfaction Analysis of E Banking Users: A field study of Conventional Bank - Yuniorita Indah Handayani; Qin Jing Jun; Agustin HP; Purnama Miftahul Rizqi (LPPM Institut Teknologi dan Sains Mandala, 2022)
The banking industry is currently growing rapidly by utilizing and optimizing management information and technology in the form of e-banking as an efficient means of a satisfying customer. Online-based services at banks are more efficient services to help customers. Technological advances have been used to attract customer for bank transactions. Therefore, customer satisfaction is a priority in banking activities. Customer satisfaction is an important factor in maintaining a competitive advantage in the era of technological development. This research is a form of replication that use the subject of bank customer of e-banking user in Jember city. The aim of the research is to determine the factors that influence customer satisfaction of e-banking users. The role of cloud service, security banking system, e-learning and service quality are four factors that can drive customer satisfaction. This research uses quantitative methods with multiple linear regression analysis. The sample use in this research amunted 125 respondents. This research find that cloud service, e-learning and service quality significantly affect on customer satisfaction, on the other hand security banking system has no effect on customer satisfaction.